Tourism in the Urban Space of the Polish Seaside Resort of Ustka - Matczak, Andrzej (Turyzm/Tourism, 2005)
The author attempts to verify a popular model of the spatial structure of a seaside resort, as well as the usefulness of a land use survey for its description. Sample studies based on direct field research were carried out in Ustka in the middle section of the Polish Baltic coast.